2021
DOI: 10.31234/osf.io/x94kv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Connections during Crisis: Adolescents’ social dynamics and mental health during COVID-19

Abstract: Adolescence is a critical period for social development, which COVID-19 has dramatically altered. Quarantined youths had limited in-person interactions with peers. The present study used an intensive longitudinal design to investigate changes in interpersonal dynamics and mental health during COVID-19. Specifically, we investigated whether the associations between different social contexts – i.e., “spillover” – changed during COVID-19, and whether changes in social interactions during COVID-19 was associated w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Therefore, these measures may have impacted young people's ability to fulfil their needs for competence, autonomy, and relatedness (Ryan & Deci, 2000) and, in turn, their mental health. Our findings are in line with the majority of previous studies that revealed a decline in adolescent mental health when comparing a pre‐COVID‐19 assessment with one assessment during the COVID‐19 pandemic (Breaux et al., 2021; Chen et al., 2021; De France et al., 2021; Gadassi Polack et al., 2021; Lee et al., 2020; Magson et al., 2021; Munasinghe et al., 2020; Rogers et al., 2021; Thorisdottir et al., 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, these measures may have impacted young people's ability to fulfil their needs for competence, autonomy, and relatedness (Ryan & Deci, 2000) and, in turn, their mental health. Our findings are in line with the majority of previous studies that revealed a decline in adolescent mental health when comparing a pre‐COVID‐19 assessment with one assessment during the COVID‐19 pandemic (Breaux et al., 2021; Chen et al., 2021; De France et al., 2021; Gadassi Polack et al., 2021; Lee et al., 2020; Magson et al., 2021; Munasinghe et al., 2020; Rogers et al., 2021; Thorisdottir et al., 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The available longitudinal studies on this topic mostly compared mental health assessments before and during the initial COVID‐19 phase. Six US studies, one Australian, one Icelandic, and one Swedish study revealed increases in different indicators of adolescent mental health problems when comparing a pre‐COVID‐19 assessment with an assessment during the COVID‐19 pandemic (Breaux et al., 2021; Chen et al., 2021; De France et al., 2021; Gadassi Polack et al., 2021; Lee et al., 2020; Magson et al., 2021; Munasinghe et al., 2020; Rogers et al., 2021; Thorisdottir et al., 2021). In contrast, a Dutch and a Norwegian study revealed fairly stable levels of mental health problems when comparing a pre‐COVID‐19 assessment with an assessment during the COVID‐19 pandemic (Achterberg et al., 2021; Burdzovic Andreas & Brunborg, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…: 2000022492; Title: “Emotion Regulation in Risk for Depression”). Study materials can be accessed online (Gadassi Polack, Sened, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%